Auditory brainstem measures and genotyping boost the prediction of literacy: A longitudinal study on early markers of dyslexia. (December 2020) - Liebig, Johanna; Friederici, Angela D.; Neef, Nicole E.; ,; Friederici, A.D.; Emmrich, F.; Brauer, J.; Wilcke, A.; Neef, N.E.; Boltze, J.; Skeide, M.; Kirsten, H.; et al.
Highlights: Multi-domain profiles advance retrospective prediction of emergent literacy. DCDC2 and KIAA0319 risk variants influence emergent spelling skills. Combined DYX2 and auditory brainstem measures enhance predictive model fits. Additional benefit of preliterate phonological awareness on predictive power. Abstract: Literacy acquisition is impaired in children with developmental dyslexia resulting in lifelong struggle to read and spell. Proper diagnosis is usually late and commonly achieved after structured schooling started, which causes delayed interventions. Legascreen set out to develop a preclinical screening to identify children at risk of developmental dyslexia. To this end we examined 93 preliterate German children, half of them with a family history of dyslexia and half of them without a family history. We assessed standard demographic and behavioral precursors of literacy, acquired saliva samples for genotyping, and recorded speech-evoked brainstem responses to add an objective physiological measure. Reading and spelling was assessed after two years of structured literacy instruction. Multifactorial regression analyses considering demographic information, genotypes, and auditory brainstem encoding, predicted children's literacy skills to varying degrees. These predictions were improved by adding the standard psychometrics with a slightly higher impact on spelling compared to reading comprehension. Our findings suggest that gene-brain-behavior profiling has the potential to determine the risk of developmental dyslexia. At the same time our results imply the need for a more sophisticated assessment to fully account for the disparate cognitive profiles and the multifactorial basis of developmental dyslexia.